Fungi increases kelp (Ecklonia radiata) remineralisation and dissolved organic carbon, alkalinity, and dimethylsulfoniopropionate (DMSP) production - Perkins, Anita K. (2023)
Fungi are key players in terrestrial organic matter (OM) degradation, but little is known about their role in marine environments. Here we compared the degradation of kelp (Ecklonia radiata) in mesocosms with and without fungicides over 45 days. The aim was to improve our understanding of the vital role of fungal OM degradation and remineralisation and its relevance to marine biogeochemical cycles (e.g., carbon, nitrogen, sulfur, or volatile sulfur). In the presence of fungi, 68 % of the kelp detritus degraded over 45 days, resulting in the production of 0.6 mol of dissolved organic carbon (DOC), 0.16 mol of dissolved inorganic carbon (DIC), 0.23 mol of total alkalinity (TA), and 0.076 mol of CO2, which was subsequently emitted to the atmosphere. Conversely, when fungi were inhibited, the bacterial community diversity was reduced, and only 25 % of the kelp detritus degraded over 45 days. The application of fungicides resulted in the generation of an excess amount of 1.5 mol of DOC, but we observed only 0.02 mol of DIC, and 0.04 mol of TA per one mole of kelp detritus, accompanied by a CO2 emission of 0.081 mol. In contrast, without fungi, remineralisation of kelp detritus to DIC, TA, dimethyl sulfide (DMS), dimethylsulfoniopropionate (DMSP) and methanethiol (MeSH) was significantly reduced. Fungal kelp remineralisation led to a remarkable 100,000 % increase in DMSP production. The observed substantial changes in sediment chemistry when fungi are inhibited highlight the important biogeochemical role of fungal remineralisation, which likely plays a crucial role in defining coastal biogeochemical cycling, blue carbon sequestration, and thus climate regulation.